2014
DOI: 10.3390/molecules191220975
|View full text |Cite
|
Sign up to set email alerts
|

Four New Furostanol Saponins from the Rhizomes and Roots of Smilax scobinicaulis and Their Cytotoxicity

Abstract: Four new furostanol saponins 1-4, along with two known furostanol saponins 5 and 6 and one known spirostanol saponin 7 were isolated from the rhizomes and roots of Smilax scobinicaulis. The structures of the new saponins were elucidated as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…16,17 The presence of the 2α,3β-dioxy-decalin moiety was supported by the oxymethine carbons at d C 71.7 (C-2) and 85.1 (C-3).…”
Section: Resultsmentioning
confidence: 98%
“…16,17 The presence of the 2α,3β-dioxy-decalin moiety was supported by the oxymethine carbons at d C 71.7 (C-2) and 85.1 (C-3).…”
Section: Resultsmentioning
confidence: 98%
“…Because steroidal saponins have been reported to possess varying cytotoxic activity against various cancer cell lines [ 17 , 18 , 19 ], in this paper, the cytotoxic activity against human SMMC-7712, Bel-7402, A549, H460, and K562 tumor cells of compounds 1 – 6 were evaluated by MTT method and all the compounds exhibited cytotoxicity with the cell lines. Compound 2 exhibited a more potent antitumor effect than 1 : it seemed that the presence of a free hydroxyl group at C-12 was more potent than a free hydroxyl group at C-17.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the spirostane or isospirostane glycosides with an oxygenated C-15 have never been reported from Smilax so far. Compounds 67 – 70 with carbonylation on C-6 were isolated from the roots and rhizomes of S. scobinicaulis , together with a spirostane glycoside 35 , and three furostane glycosides 89 – 91 [ 28 ]. Compounds 76 and 77 , isolated from the root of S. officinalis , are the diastereoisomers with opposite configuration at C-5 [ 29 ].…”
Section: Chemistry Of Steroidal Saponinsmentioning
confidence: 99%
“…Only compound 38 possessed significant cytotoxicities with IC 50 values of 3.70, 5.70 and 3.64 μM, respectively [ 21 ]. Another cytotoxic compound is isospirostane glycoside 32 , which displayed potent cytotoxicities against the Hela and SMMC-7221 cancer cell lines with IC 50 values of 9.73 ± 1.64 and 21.54 ± 1.64 μM, respectively [ 28 ]. The above results indicated that the hydroxyl substitutions on C-6 or C-17 of isospirostane glycosides decrease the cytotoxicities.…”
Section: Biological Activities Of Steroidal Saponinsmentioning
confidence: 99%
See 1 more Smart Citation